Method of analogy (Uslub Al-Tashbih)in Arabic and Chinese rhetoric : the analysis and comparative study - Li Ying (Tanjong Malim, 2019)
Method of analogy (Uslub Al-Tashbih)in Arabic and Chinese rhetoric : the analysis and comparative study by Li Ying